Endoscopic Sphenopalatine Artery Cauterization Under Local Anesthesia for Posterior Epistaxis: A Prospective Cohort Study of its Tolerability and Efficacy - Urmila Gurung; Narmaya Thapa; Sajish Khadgi (Turkish Archives of Otorhinolaryngology)
Objective: To assess the tolerability and efficacy of endoscopic sphenopalatine artery cauterization (ESPAC) under local anesthesia (LA) in managing posterior epistaxis. Methods: It was a prospective, cohort study, conducted in the Otorhinolaryngology Department of a tertiary-level hospital. Patients aged 18 years or above with posterior epistaxis who underwent ESPAC under LA were included. The tolerability of the procedure was reflected by the intraoperative pain measured using an 11-point numerical rating scale while the rebleed rate up to three months postoperatively denoted its efficacy. Results: A total of 35 patients, 23 males and 12 females, aged 31 to 86 years (mean 57.42 ± 12.94) were included. Five out of 35 (14.2%) patients needed additional procedures besides ESPAC; 82.8% (29/35) had pterygopalatine fossa (PPF) block before ESPAC. The numerical rating scale reflecting the intraoperative pain ranged from 1 to 7 with a mean of 3.6 (± 1.7). The mean score was slightly higher in females than in males. Similarly, those who did not receive PPF block had a higher mean score than those who received it; however, the differences were not statistically significant. Meanwhile, the mean score was the same (3.6) irrespective of any additional procedure besides ESPAC. Amongst the 30 patients who completed the three-month follow-up, two patients rebled, so the overall success rate amounted to 93.3% in three months. Conclusion: Based on the outcome of this study, ESPAC under LA for posterior epistaxis is well tolerated and is as efficacious as under general anesthesia.